WTO in History: a Ticking Bomb - Nada Najiha (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The World Trade Organization, named for the multilateral trade institution, was struggling with various critical issues both in the past, and for the future. This research would explain how the history pace could have given some unanswered questions through looking back at the previous multilateral trade institution and given an underlined notes for some practical solutions. WTO is the highest accomplishment for the trade sector, yet. But unfortunately, the commitment of sticking through the principles were often weakening years by years, not in a quick move, but specifically, in the end, we would know that it becomes stagnant and no longer provides all the needs. Regional Trade Agreements (RTAs) were the best choice, yet, looking at Article XXIV GATT, it would help much more.Keywords: GATT; Trade Institution; World Trade Organization AbstrakWorld Trade Organization, merupakan organisasi perdagangan internasional, yang kini, berada di tengah gejolak dengan berbagai isu yang berdampak pada iklim perdagangan dunia. Tulisan ini membahas mengenai bagaimana permasalahan yang terjadi pada tubuh World Trade Organization sekarang ini terjawab dengan melihat perkembangan organisasi itu sendiri dari tiap kurun waktu. World Trade Organization adalah pencapaian tertinggi yang dibangun pada bidang perdagangan dunia. Namun, komitmen untuk tetap berpegang teguh pada aturan-aturannya seakan menjadi semakin melemah dari tahun ke tahun. Hal ini tidak terjadi secara simultan, namun, kita dapat melihat bahwa organisasi ini cenderung bergerak di tempat dan tidak lagi mengakomodir negara-negara anggotanya. Perjanjian Perdagangan Regional merupakan solusi yang terbaik, untuk saat ini, merujuk pula pada Pasal XXIV GATT, tampaknya, ragam kesepakatan ini akan memberi jalan keluar.Kata Kunci: GATT; Organisasi Perdagangan; World Trade Organization